The Membrado Library: readings of a Bajoaragonese family in the 18th century and the first half of the 19th century - Gimeno Puyol, María Dolores (Revista General de Información y Documentación, 2018)
Successive generations of the Membrado, a landed family from the Bajoaragonese town of Belmonte established a library that currently holds 106 titles. This article carries out its cataloguing and analysis. On the one hand, its configuration process throughout the 18th century and the first half of the 19th century is revised, focusing on the ways the ways the books were obtained or their provenance, and also examines some reading practices, as well as their intentionality. On the other hand, the present subjects are classified and reviewed, pointing out a cycle of readings from the learning of the first letters to the ecclesiastical or legal studies together with later books dedicated to leisure and professional or practical purposes. This morphology and other material aspects (authors, editing places, languages, formats) reveal the mental universe of its readers, provide data on a scholarly environment in rural areas at that time and highlight the value of the book in personal formation and social promotion.
Keywords: Library; Uses of the book; Reading; 18th century; 19th century; Bajo Aragón